Impacto financiero de la implementación de un sistema de gestión de calidad y la incidencia actual respecto a la reputación corporativa, en una empresa florícola - Barén Sabando, Carlos Alejandro (2021)
This study was carried out in order to analyze the financial impact of the implementation of a Quality Management System (QMS) and its impact on corporate reputation in a flower company, for the contribution of competitive advantage in the market. The ISO: 9001 Standards represent a tool for the application of quality, since they present the requirements of a Quality Management System. Reputation supposes being an intangible asset of a company, of a fundamental value in management, it also has links with identity, image and brand. In relation to the above, the methodology used is composed of surveys carried out through Google Forms online forms, under the content validity of the Lawshe model, modified by Tristán and the SPSS program was applied for the statistical analysis to determine the coefficient of Pearson correlation between variables. It was possible to know how they affect each other; at present, a relationship exists between leadership, planning with the results in the profitability of the company; and between leadership, planning, support, operation, performance evaluation and improvement, with the efficiency of the flower business activity. The impact of the implementation and certification of the Quality Management System is understood, since, as shown by the correlations, the decreases and increases in compliance with the ISO: 9001 Standard are also reflected in the economic results.